Agency, Education and Networks : Gender and International Migration from Albania - Stecklov, Guy; Carletto, Calogero; Azzarri, Carlo; Davis, Benjamin (World Bank, Washington, DC, 2012)
This paper examines the causes and dynamics of the shift in the gender composition of migration, and more particularly, in the access of women to migration opportunities and decision making. The context of the analysis is Albania, a natural laboratory for studying migration developments given that out-migration was practically eliminated from the end of World War II to the end of the 1980s. The authors use micro-level data from the Albania 2005 Living Standards Measurement Study including migration histories for family members since migration began. Based on discrete-time hazard models, the analysis shows an impressive expansion of female participation in international migration. Female migration, which is shown to be strongly associated with education, wealth, and social capital, appears responsive to economic incentives and constraints. Yet, using unique data on the dependency of female migration to the household demographic structure as well as the sensitivity of female migration to household-level shocks, the authors show that it is the households themselves that are the decision-making agents behind this economic calculus and there is little to suggest that increased female migration signals the emergence of female agency.